2021
DOI: 10.1098/rspb.2021.0866
|View full text |Cite
|
Sign up to set email alerts
|

The anti-predation benefit of flash displays is related to the distance at which the prey initiates its escape

Abstract: Flash behaviour is widespread in the animal kingdom and describes the exposure of a hidden conspicuous signal as an animal flees from predators. Recent studies have demonstrated that the signal can enhance survivorship by leading pursuing predators into assuming the flasher is also conspicuous at rest. Naturally, this illusion will work best if potential predators are ignorant of the flasher's resting appearance, which could be achieved if the prey flees while the predator is relatively far away. To test this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…S10 for the results when the binary classification was used). Thus, macroevolutionary studies on animal coloration should take into account these underappreciated hidden signals, which are both common and widespread across the animal kingdom ( 13 , 43 , 44 ), to advance our understanding of the evolution of antipredator defenses. Indeed, many animal taxa such as snakes, fishes, and a variety of arthropods (see fig.…”
Section: Discussionmentioning
confidence: 99%
“…S10 for the results when the binary classification was used). Thus, macroevolutionary studies on animal coloration should take into account these underappreciated hidden signals, which are both common and widespread across the animal kingdom ( 13 , 43 , 44 ), to advance our understanding of the evolution of antipredator defenses. Indeed, many animal taxa such as snakes, fishes, and a variety of arthropods (see fig.…”
Section: Discussionmentioning
confidence: 99%
“…Teasing apart the evolutionary drivers shaping warning signals is an important next step to understand the importance of flash (and deimatic) behaviour as an antipredator defence. In amphibians, the evolution of cryptic to aposematic colours involves hidden colour signals as an intermediate stage (Loeffler-Henry, Kang & Sherratt, 2023).…”
Section: Misleading Motion Signalsmentioning
confidence: 99%
“…The predator may assume that the prey has a conspicuous appearance and would continue the search for the conspicuous features of the prey when the signals are hidden (Cott, 1940; Edmunds, 1974; Martin et al ., 2022). Factors such as prey body size (Bae et al ., 2019; Caro, Raees & Stankowich, 2020; Emberts et al ., 2020) and the distance between prey and predator (Loeffler‐Henry, Kang & Sherratt, 2021) can influence the efficacy of flash behaviour. For instance, contrasting colour patterns that may be effective in flash behaviour were associated with larger body size in some insect groups (Kang, Zahiri & Sherratt, 2017; Loeffler‐Henry, Kang & Sherratt, 2019; Caro et al ., 2020).…”
Section: Misleading Motion Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a ‘proof of concept’ experiment demonstrated that the confusion effect of flash behaviour alone is sufficient to prevent attacks (Loeffler‐Henry et al ., 2018). Moreover, flash displays may be more effective in reducing predation when the signaller flees from a distance, so that the signaller's cryptic resting state is not observed (Loeffler‐Henry, Kang & Sherratt, 2021). Since hidden signals are less likely to frighten the observer when exposed from a distance, then deimatic and flash displays are functionally distinct and may often be incompatible.…”
Section: What Is Deimatic Behaviour?mentioning
confidence: 99%